2008
DOI: 10.1530/rep-08-0226
|View full text |Cite
|
Sign up to set email alerts
|

Production of donor-derived sperm after spermatogonial stem cell transplantation in the dog

Abstract: Spermatogonial stem cell transplantation (SSCT) offers unique approaches to investigate SSC and to manipulate the male germline. We report here the first successful performance of this technique in the dog, which is an important model of human diseases. First, we investigated an irradiation protocol to deplete endogenous male germ cells in recipient testes. Histologic examination confirmed O95% depletion of endogenous spermatogenesis, but retention of normal testis architecture. Then, 5-month-old recipient dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 45 publications
(67 reference statements)
4
88
0
Order By: Relevance
“…Brinster and colleagues provided the initial demonstration that testicular cells from a fertile mouse could be transplanted into the seminiferous tubules of an infertile recipient, in which they produced complete spermatogenesis and sometimes restored fertility (12)(13)(14). Regeneration of spermatogenesis following SSC transplantation has now been established in several animal models, including rodents, goats, sheep, pigs, dogs, and monkeys (13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Brinster and colleagues provided the initial demonstration that testicular cells from a fertile mouse could be transplanted into the seminiferous tubules of an infertile recipient, in which they produced complete spermatogenesis and sometimes restored fertility (12)(13)(14). Regeneration of spermatogenesis following SSC transplantation has now been established in several animal models, including rodents, goats, sheep, pigs, dogs, and monkeys (13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…SSC transplantation has proven effective for regenerating spermatogenesis and fertility in small and large animal models (Brinster and Avarbock, 1994;Ogawa et al, 2000;Shinohara et al, 2001;Nagano et al, 2001;Brinster et al, 2003;Honaramooz et al, 2003;Orwig and Schlatt, 2005;Mikkola et al, 2006;Kim et al, 2008). Clinical translation of this technique is imminent and may provide hope for future fertility in cases where there are no other options to preserve and/or restore fertility, such as prepubertal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although prepubertal boys are not making sperm, their testes contain SSCs that are poised to initiate spermatogenesis at puberty (Ehmcke et al, 2006;Culty, 2009;Wu et al, 2009). In animal models (rodents, pigs, goats and dogs), transplantation of SSCs into the testes of infertile males can lead to restoration of spermatogenesis (Brinster and Avarbock, 1994;Ogawa et al, 2000;Shinohara et al, 2001;Nagano et al, 2001;Brinster et al, 2003;Honaramooz et al, 2003;Orwig and Schlatt, 2005;Mikkola et al, 2006;Kim et al, 2008). Stem cells from all ages, newborn to adult, are competent to produce complete spermatogenesis following transplantation into recipient testes (Shinohara et al, 2001;Ryu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As reported, SSCs from domestic species could colonize and proliferate in host mouse testes after transplantation, but could not give rise to entire spermatogenesis , Izadyar et al 2002, Oatley et al 2002, Kim et al 2006; Table 2), probably due to the phylogenetic disparity between donors and hosts. Later, allogeneic transplantation of SSCs was tested in boars, bulls, goats, sheep, and dogs (Honaramooz et al 2002a, Izadyar et al 2003, Herrid et al 2006, 2009b, Kim et al 2008, and the development of the donor germ cells was observed in those recipients of homogeneous species ( Fig. 2A and Table 2).…”
Section: Transplantation Of Sscs From Domestic Animalsmentioning
confidence: 99%